First record of Kamimuria (Plecoptera: Perlidae) from Hainan Island of China, with description of K. hainana n. sp. - Li, Weihai; Wang, Liuhao; Yu, Hao (Zootaxa, 2012)
The genus Kamimuria is reported from Hainan Island, China for the first time with K. hainana sp. nov. described as new to science. The taxonomic relationship with similar species is discussed.